Interactions Between Hantavirus Nucleoprotein and Glycoproteins: A Quantitative Fluorescence Microscopy Study - Amit Koikkarah Aji; Titas Mandal; Salvatore Chiantia (Viruses)
Orthohantaviruses are tri-segmented negative-sense RNA viruses that can cause severe pathologies in humans. Currently, limited information exists on the molecular interactions driving orthohantavirus assembly in infected cells. Specifically, it is not clear how its glycoproteins (i.e., Gn and Gc) interact with other viral or host molecules. In this study, we use one- and two-color Number and Brightness fluorescence microscopy approaches to quantitatively characterize the interactions between orthohantavirus glycoproteins and the nucleoprotein in transfected cells. Our results indicate that orthohantavirus nucleoprotein homo-interactions are strongly affected by the host environment. Furthermore, we report evidence of Gc–nucleoprotein interactions, based on (i) the high fluorescence cross-correlation between these two proteins and (ii) the increased Gc-Gc interactions observed in the presence of nucleoprotein. Finally, experiments on a Gc deletion mutant suggest that the observed protein–protein interactions are mediated by the cytoplasmic tail of Gc. In conclusion, this study provides new insights into the role of the interactions between orthohantavirus glycoproteins and nucleoprotein in the context of viral assembly.